2019
DOI: 10.3390/ijms20092363
|View full text |Cite
|
Sign up to set email alerts
|

A Symphony of Signals: Intercellular and Intracellular Signaling Mechanisms Underlying Circadian Timekeeping in Mice and Flies

Abstract: The central pacemakers of circadian timekeeping systems are highly robust yet adaptable, providing the temporal coordination of rhythms in behavior and physiological processes in accordance with the demands imposed by environmental cycles. These features of the central pacemaker are achieved by a multi-oscillator network in which individual cellular oscillators are tightly coupled to the environmental day-night cycle, and to one another via intercellular coupling. In this review, we will summarize the roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 406 publications
(923 reference statements)
0
23
0
Order By: Relevance
“…For example, we found that Dh31 51 ; Pdf 01 double mutants, but not Dh31 51 or Pdf 01 single mutants, retain mature oocytes at 29˚C, resulting in decreased egg laying ( S5C Fig). Both Dh31 and Pdf regulate circadian rhythm [62], and Drosophila egg laying is circadian regulated [63]. Although ablation of PDF-producing neurons does not affect egg laying circadian rhythm [64], it is possible that DH31 and PDF may act in redundant pathways to regulate circadian-regulated egg-laying behavior.…”
Section: Complex Roles Of Neuropeptide Signaling In Whole-body Physiomentioning
confidence: 99%
“…For example, we found that Dh31 51 ; Pdf 01 double mutants, but not Dh31 51 or Pdf 01 single mutants, retain mature oocytes at 29˚C, resulting in decreased egg laying ( S5C Fig). Both Dh31 and Pdf regulate circadian rhythm [62], and Drosophila egg laying is circadian regulated [63]. Although ablation of PDF-producing neurons does not affect egg laying circadian rhythm [64], it is possible that DH31 and PDF may act in redundant pathways to regulate circadian-regulated egg-laying behavior.…”
Section: Complex Roles Of Neuropeptide Signaling In Whole-body Physiomentioning
confidence: 99%
“…In vivo and in vitro studies of the SCN showed that calcium influx induces the activity of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), resulting in the activation of protein kinase A (PKA), and protein kinase C (PKC). These kinases then phosphorylate CREB in a circadian manner ( Agostino et al, 2004 ; Hegazi et al, 2019 ). The phosphorylated CREB translocates into the nucleus where it recognizes the CRE of the Per genes promoters and induces their expression ( Lee et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to VIP, other neurotransmitters such as vasopressin (AVP), gamma-aminobutyric acid (GABA), and gastrin-releasing peptide (GRP) have been described to modulate synaptic SCN coupling and activity rhythms in mice (for review, see Ref. [202]).…”
Section: Coupling Within the Scnmentioning
confidence: 99%